Dosimetric study of TrueBeam single-isocenter vs. Halcyon dual-isocenter VMAT radiotherapy plans for postoperative left-sided breast cancer - Chaojun Chai; Kainan Shao; Guoping Shan; Pu Li; Fenglei Du; Yiwei Yang (BMC Cancer)
Abstract Background This study compared the plan quality and execution efficiency of VMAT plans using TrueBeam single-isocenter and Halcyon dual-isocenter systems for postoperative left-sided breast cancer, providing evidence for the selection and application of radiotherapy methods after breast cancer surgery. Methods Twenty postoperative left-sided breast cancer patients treated at Zhejiang Cancer Hospital from January 2020 to August 2022 were included in the study. Using the RayStation 9 A system, TrueBeam single-isocenter (T group) and Halcyon dual-isocenter (H group) VMAT plans were created. The study compared PTV (Planning Target Volume) conformity index (CI), homogeneity index (HI), mean and maximum doses, dose to organs at risk (OAR), monitor units (MU), beam-on time, and plan complexity between the groups. Results Both groups’ plans met clinical objectives with good dose distribution and target coverage. Significant statistical differences were observed in the PTV maximum dose (Dmax), mean dose (Dmean), and D50 between the two groups (P < 0.05), with the H group outperforming the T group. There was no statistically significant difference in CI and HI between the two groups (P > 0.05). The OAR doses were lower in the H group compared to the T group, with significant statistical differences observed in heart Dmean, left lung (Dmean, V5, V20, V30), lungs (Dmean, V5, V20, V30), and humeral head Dmax (P < 0.05), and there was no statistically significant difference in heart (V30, V40), spinal cord Dmax, and right breast Dmean (P < 0.05). In terms of plan quality assessment, the total MU for the H group was significantly higher (1066.704 ± 135.183) than that for the T group (772.992 ± 104.023), with extremely significant statistical differences (P < 0.01). The beam-on time for the H group was significantly longer (101.328 ± 9.359 s) than that for the T group (53.535 ± 12.655 s), with extremely significant statistical differences (P < 0.01). The plan complexity for the H group was significantly higher (0.101 ± 0.009 cm−1) than that for the T group (0.068 ± 0.009 cm−1), with extremely significant statistical differences (P < 0.01). Conclusions The study found that Halcyon dual-isocenter VMAT plans offered better PTV uniformity and coverage while protecting OARs more effectively. Despite higher MU, beam-on time, and plan complexity, the H group’s dosimetric advantages and reduced manual positioning errors make it a safe and effective treatment option for postoperative breast cancer.